2016
DOI: 10.1007/s10608-016-9806-9
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Non-Suicidal Self-Injury Scale: Initial Psychometric Validation

Abstract: The current study examined the psychometric properties of the Impact of Non-Suicidal Self-Injury Scale (INS), a scale developed to assess the social, behavioral, and emotional consequences of engaging in non-suicidal self-injury (NSSI). University students (N=128) who endorsed a history of NSSI were administered the INS, as well as measures of hypothesized convergent and divergent validity. Results suggested that the INS is best conceptualized as a one-factor scale, and internal consistency analyses indicated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 74 publications
(70 reference statements)
1
10
0
Order By: Relevance
“…Emotion reactivity was stronger in the NSSI group than the non-NSSI group. This finding is consistent with some previous studies (28,29,39,57), which showed that people with NSSI behavior have a higher level of arousal, which is related to their emotion regulation and response to emotions, leading to maladaptive NSSI behaviors (28).…”
Section: Discussionsupporting
confidence: 93%
“…Emotion reactivity was stronger in the NSSI group than the non-NSSI group. This finding is consistent with some previous studies (28,29,39,57), which showed that people with NSSI behavior have a higher level of arousal, which is related to their emotion regulation and response to emotions, leading to maladaptive NSSI behaviors (28).…”
Section: Discussionsupporting
confidence: 93%
“…If these are considered to be indicators of distress or impairment, the consequences of NSSI are likely to be viewed as more problematic. 58 Going forward it will be important to clarify just how Criterion E should be evaluated and what forms of evidence are most valid.…”
Section: Nssi-d In Dsm-5mentioning
confidence: 99%
“…Commensurately, mood repair is among the most frequently endorsed functions of many maladaptive behaviors, including NSSI (Klonsky, 2007). However, contrahedonic increases in negative affect and reductions in positive affect, including increased negative self-consciousness, are also commonly endorsed consequences of NSSI (Burke, Ammerman, Hamilton, & Alloy, 2017). Therefore, a central problem is to articulate more precisely the relationship between AR and maladaptive behavior.…”
mentioning
confidence: 99%